The Analysis of Multiple Intelligences of Students Through Project Based Learning Class Activities - Siti Habibah; Aceng Haetami; Sumarni Rumfot; Muhammad Ridhwan; Mas’ud Muhammadiah (Journal on Education, 2023)
This study's goal was to examine how the project-based learning paradigm affected various components of intelligence and the effectiveness of students' multiple intelligences. The research sample consisted of 30 XI students. Descriptive research methodology is employed. Interviews, observation, and questionnaires were the tools employed. The findings demonstrated that all facets of the kids' multiple intelligences, including logical-mathematical, visual-spatial, linguistic, body-kinesthetic, musical, intrapersonal, and naturalist intelligence, were present. The category for interpersonal quotient is quite good. The majority of student intelligence falls into the good group, specifically in the areas of logical-mathematical, linguistic, bodily-kinesthetic, intrapersonal, and naturalist intelligence. Pupils' musical intelligence is subpar, but their visual-spatial intelligence is pretty strong.